Activity of steroid receptors in the ovaries in women with and without adenomyosis and hyperplastic processes of the endometrium in menopause. - Goncharenko, G. Yu. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. Adenomyosis (AM) is a relevant problem in modern medicine. Manifestations of AM do not subside against the background of hypoestrogens. Some studies indicate local hyperteriogenicity and autonomous growth of AM foci. However, there are no reliable data on the activity and effect of the steroid hormones of the ovaries on the pathogenesis of AM. Of especial importance is this problem in women in menopause. It is of interest to study immunohistochemical (IHC) features of the ovarian tissue cells in women in the presence of AM and associated pathology of the endometrium. Objective. Investigation of IHC activity of the steroid receptors in the ovaries of women with AM and hyperplastic endometrial processes (endometrial hyperplasia (HPE) and endometrioid endometrium carcinoma (ECE)) without menopause and its role in the pathogenesis of this existence. Materials and methods. The material included removed ovaries of 30 patients (52-73 years) diagnosed with AM in combination with and without hyperplastic processes of the endometrium. The IHC studies were conducted for markers ER, PR and AR. Results. IHC studies have found that there was no reaction to ER markers with IHC among most women. On assessing the expression of ovarian cancer in women with AM and HPE a weak intensity level and moderate - the prevalence of coloration was more often revealed. The similar situation was observed in other groups of women. The analysis of IHC of the reaction with AR showed that in cases of AM and HPE the intensity of 1 point and the prevalence of coloration in 2 points, in contrast to the group of ECE was more frequent, where the most common were 2 and 4 points, respectively. Intermediate position was occupied by women with age-related changes in the endometrium. Conclusions. In postmenopausal women, due to the noticeable decrease in estrogen synthesizing function, the ovaries do not affect the pathogenesis of AM as a source of hyperestrogenism. The ability of the ovaries to develop progesterones indicates its need as one of the elements of AM development. In postmenopause, the preservation of the androgene-producing ovarian function plays a leading role in the pathogenesis of AM as a source of further synthesis of estrogen.